Tomas Hammar, Democracy and the Nation State. Aliens, Denizens and Citizens in a World of International Migration, Research in Ethnic Relations Series, Aldershot: Gower, 1990, 226 s. - Hamburger, Charlotte (Politica, 1992)
-